Depths of uncertainty for deep-sea policy and legislation. (January 2019) - Folkersen, Maja Vinde; Fleming, Christopher M.; Hasan, Syezlin
Highlights: A social valuation perspective on the deep sea's economic value. Global perspective needed for environmental impact assessments (EIA) of deep-sea mining activities. Further research required into the relationship between human actions and deep-sea value. Ecosystem functioning of the deep sea requires further research and understanding. Abstract: In comparison to terrestrial and coastal ecosystems, much remains unknown about the deep sea's ecosystems and their economic value. This is of concern on at least three fronts. First, the deep sea forms the majority of the ocean's marine systems and contributes substantially to global fish stocks (Danovaro et al., 2017; Drazen and Sutton, 2017). Second, it is essential for the functioning of global biogeochemical cycles, and underpins the sustenance of terrestrial ecosystems and human life (Armstrong et al., 2012). Third, the deep sea faces increased pressure from human activity in the form of deep-sea mining (DSM) (The World Bank, 2016). Based upon lessons drawn from a recent systematic review and meta-analysis published in Marine Policy (Folkersen et al., 2018), this letter discusses four main directions for future research into economic valuation, policymaking and legislation pertaining to the deep sea. First, the valuation perspective adopted for policy and decision-making on deep-sea resources needs to be defined clearly. Second, strategic environmental assessments (SEAs) and environmental impact assessments (EIAs) of DSM activities need to examine the potential global environmental damage from DSM, rather than examine impacts restricted to the geographical site in which mining takes place. Third, the interdependence between anthropogenic behaviour and economic value generated by the deep sea requires further investigation. Fourth, in addition to the valuation of specific ecosystem goods and services, the ecosystem functioning of the deep sea should also be valued. Improving our understanding of the value that the deep sea provides to human societies can facilitate sustainable resource-use, effective environmental management, and prevent severe and irreversible damage to the deep sea's ecosystems.